Cumulative suppressive index as a predictor of relapse free survival and overall survival in Human Papilloma Virus‐negative oral squamous cell carcinomas with negative resection margins. Issue 2 (23rd October 2020) - Hum, Lauren; Bethmann, Daniel; Feng, Zipei; Chang, Shu‐Ching; Eckert, Alexander; Ballesteros‐Merino, Carmen; Keschke, Claudia; Kappler, Matthias; Bifulco, Carlo B.; Wickenhauser, Claudia; Seliger, Barbara; Fox, Bernard A.; et al.
Abstract: Background: This study aimed to analyze margin status and the impact of the immune elements on recurrence in patients with oral squamous cell carcinoma (OSCC), employing a prognostic biomarker, cumulative suppressive index (CSI), which reflects FoxP3+, PD‐L1+, and CD8+ cell spatial relationships in the tumor microenvironment. Methods: Cox proportional hazards regression was used to evaluate the interactive effect of the margin by CSI discrepancy (high, 3‐4 vs low, 0‐2) on recurrence free survival (RFS) and overall survival (OS) in 119 patients with stage I to IVA OSCC. Results: In cases with negative margins, multivariable analysis showed high CSI was significantly associated with worse RFS (HR = 2.59, 95% CI [1.03, 6.49], P = .04) and OS (HR = 5.49, 95% CI [1.48, 20.35], P = .01) compared to low CSI. However, high CSI was not significantly associated with recurrence in cases with positive margins. Conclusions: Immune architecture analysis can augment our current histopathological risk assessment of margin status.